Pengaruh Board Independence, Firm Size, Debt To Equity Ratio, Net Profit Margin Terhadap Kebijakan Dividen Pada Perusahaan (Sub Sektor Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bei 2009 – 2018) - Desiana Dinda Nur Aziza; Riana R Dewi; Rosa Nikmatul Fajri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2020)
Dividend policy is a profit right used by investors where the profit will be shared or retained for reinvestment. The population used by researchers are 8 food and beverage companies listed on the Indonesia Stock Exchange in 2009-2018. Sampling by purposive sampling technique, 8 companies were selected. Data analysis techniques in this study were multiple linear regression. This study obtained the results of board independence and net profit margin affect the dividend policy, while the firm size and debt to equity ratio do not affect the dividend policy. The benefits of research are providing additional information to researchers who will develop knowledge in the field of financial accounting.